Planejamento de lavra com foco no sequenciamento operacional de um sistema de lavra por correias em uma mina a céu aberto - Douglas Emerich Gonçalves Oliveira (2023)
The transportation of materials using off-highway trucks in open pit mines is widespread in the world, as it has advantages such as cost reduction through economies of scale and high operational flexibility. However, some open pit mines adopt belt conveyor systems during the mining phase to transport materials between the mining fronts and the processing plants. This modality, known as belt mining, was pioneered in Brazil by Samarco at the Alegria Complex mines in Minas Gerais. Conveyor belt mining has advantages over the use of trucks, among which are lower operating costs and environmental benefits related to the decarbonization of the operations, which are issues that are much discussed today. For the conveyor belt mining to be feasible and maximized in the operations it is necessary to have a detailed long-term planning focused on it, considering the development design and evolution of the conveyor belt beds over the years to make its execution feasible. With the objective of maximizing conveyor belt mining at Samarco, a medium-term mining plan was developed with a great level of detailing of the belt conveyors and their evolution over the years and based on this, the mass to be mined by belts was calculated for the scheduling taking in consideration the installed capacity of the systems. The results show that the maximization of belt mining in the medium and long term allows the mining of 45.9 million tons by this method between 2023 and 2027, reaching a share of up to 60% of the ROM in some periods. The results, therefore, confirm the importance of a mining planning focused on enabling its utilization and maximization.